Gross Worker Flows in the Presence of Informal Labor Markets : The Mexican Experience 1987-2002 - Bosch, Mariano; Maloney, William (World Bank, Washington, DC, 2012)
This paper applies recent advances in the study of labor market dynamics to a representative developing country with a large informal or unregulated sector, Mexico. It studies quarterly gross flows of workers over a 15-year period that includes two recoveries and recessions, including the celebrated 1995 Tequila crisis. It finds, first, that the formal or modern salaried sector shows the same procyclical job finding rate and mildly countercyclical separation behavior identified in the recent U.S. literature, and relative wage rigidity, both consistent with Shimer (2005a) and Hall (2005). The unregulated informal sector, however, shows reasonable acyclicality in the job finding rate coupled with sharp countercyclical movements in the job separation rate, consistent with standard small firm dynamics and Davis and Haltiwanger (1992 and 1999). This interaction of regulatory coverage and firm sizes, and patterns of gross worker flows thus sheds suggestive light on the roots of countercyclical job finding behavior in the U.S. literature. Second, the patterns of worker transitions between formality and informality correspond to the job-to-job dynamics observed in the United States and not to the traditional idea of informality constituting the inferior sector of a segmented market. That said, the countercyclical job finding in the formal sector combined with the acyclical job finding in informality does lead to the latter absorbing relatively more labor during downturns. Third, aggregate employment dynamics vary across the Tequila crisis and the later 2001 slowdown, suggesting that not only the composition of employment, but the nature of the shocks is important to understanding how the labor market adjusts.